\(\Leftrightarrow5\cdot\dfrac{5-4-2}{20}< \dfrac{x}{20}< =3\cdot\dfrac{10-5-4}{20}\)
=>-1/20<x/20<=3/20
=>-1<x<=3
hay \(x\in\left\{0;1;2;3\right\}\)
\(\Leftrightarrow5\cdot\dfrac{5-4-2}{20}< \dfrac{x}{20}< =3\cdot\dfrac{10-5-4}{20}\)
=>-1/20<x/20<=3/20
=>-1<x<=3
hay \(x\in\left\{0;1;2;3\right\}\)
Tính giá trị biểu thức
a, \(\dfrac{5.8-5.6}{10}\) b, \(\dfrac{\left(-4\right)^2}{5}\) B = \(\dfrac{3}{7}+\left(\dfrac{-1}{5}+\dfrac{-3}{7}\right)\) C = \(\left(6-2\dfrac{4}{5}\right).3\dfrac{1}{8}-1\dfrac{3}{5}:\dfrac{1}{4}\)
D = \(\left(\dfrac{-5}{24}+0,75+\dfrac{7}{12}\right):\left(-2\dfrac{1}{8}\right)\) E = \(\dfrac{-5}{7}.\dfrac{2}{11}+\dfrac{-5}{7}.\dfrac{9}{11}+1\dfrac{5}{7}\) F = \(\dfrac{6}{7}+\dfrac{5}{8}:5-\dfrac{3}{16}.\left(-2\right)^2\)
Cho A = \(\dfrac{\left(3\dfrac{2}{15}+\dfrac{1}{5}\right):2\dfrac{1}{2}}{\left(5\dfrac{3}{7}-2\dfrac{1}{4}\right):4\dfrac{43}{56}}\) ; B = \(\dfrac{1,2:\left(1\dfrac{1}{5}.1\dfrac{1}{4}\right)}{0,32+\dfrac{2}{25}}\)
Chứng minh rằng A= B
a,\(\dfrac{-4}{5}-\left(\dfrac{2}{3}x+1\dfrac{1}{4}\right)=\dfrac{2}{7}\)
b\(\dfrac{5}{6}+\left(\dfrac{3}{4}-\dfrac{1}{2}:x\right)=\dfrac{-2}{3}\)
c\(\left(\dfrac{4}{5}x-1\dfrac{1}{3}\right):\dfrac{3}{4}=0,7\)
d\(\dfrac{5}{6}-\dfrac{3}{4}x=1\dfrac{1}{3}+0,5x\)
giúp mình nhé mình đang cần gấp
tính M = \(\dfrac{1,6:\left(1\dfrac{3}{5}.1,25\right)}{0,64-\dfrac{1}{25}}+\dfrac{\left(1,08-\dfrac{2}{25}\right):\dfrac{4}{7}}{\left(5\dfrac{5}{9}-2\dfrac{1}{4}\right).2\dfrac{2}{17}}+0,6.0,5:\dfrac{2}{5}\)
1. Thực hiện phép tính
a. \(25\%-\dfrac{5}{4}+1\dfrac{5}{6}\)
b. \(75\%:2\dfrac{1}{5}-\left(0,5\right)^2.\left(-7\right)+2.5\left(7\dfrac{2}{3}-5\dfrac{2}{3}\right)\)
c. \(45:2\dfrac{4}{7}+50\%-1,25\)
d. \(350\%:\dfrac{105}{24}+4\dfrac{5}{6}:2-\left(0,5\right)^2.30\%\)
e. \(4\dfrac{2}{5}.0.5-1\dfrac{3}{7}.14\%+\left(-0,8\right)\)
f. \(2\dfrac{3}{4}.\left(-0,4\right)-1\dfrac{3}{5}.2,75+\left(-1,2\right);\dfrac{4}{11}\)
tìm x
a\(\dfrac{2}{3}x-\dfrac{5}{6}=-1\dfrac{1}{2}x+0,75\)
b\(\left(5x-3\right).\left(2x+5\right)=0\)
c\(\left(\dfrac{5}{6}:x-1\dfrac{1}{4}\right)^4=\dfrac{81}{16}\)
d\(\left|\dfrac{2}{5}x-0,2\right|.1\dfrac{1}{4}-2=1,5\)
giúp mình nhé
Bài 2:Tìm x biết:
a)\(\dfrac{1}{7}+x=\dfrac{-2}{3}\)
b)\(\dfrac{-2}{3}:x=\dfrac{-5}{6}\)
c)\(\left\{\dfrac{3}{5}-2x\right\}.\dfrac{5}{8}=1\)
d)\(\dfrac{3}{4}+\dfrac{2}{5}x=\dfrac{29}{60}\)
e)\(\dfrac{3}{4}+\dfrac{1}{4}:x=\dfrac{2}{5}\)
f)\(\dfrac{11}{12}-\left(\dfrac{2}{5}+x\right)=\dfrac{2}{3}\)
g)\(\left|X+\dfrac{1}{3}\right|-4=\dfrac{-1}{2}\)
h)\(\left(\dfrac{1}{32}\right)^x.8^{2x}=512\)
i)\(5,3x+\left(-3,3\right)x+1,7=-4,9\)
Tính
a, 4\(\times\left(-\dfrac{1}{2}\right)^3-2\times\left(-\dfrac{1}{2}\right)^2+3\times\left(-\dfrac{1}{2}\right)+1\)
b, \(\dfrac{4^6\times9^5+6^9\times120}{-8^4\times3^{12}+6^{11}}\)
c, \(\dfrac{155-\dfrac{10}{7}-\dfrac{5}{11}+\dfrac{5}{23}}{403-\dfrac{26}{7}-\dfrac{13}{11}+\dfrac{12}{23}}+\dfrac{\dfrac{3}{5}+\dfrac{3}{13}-0,9}{\dfrac{7}{91}+0,2-\dfrac{3}{10}}\)
d,\(\dfrac{30\times4^7\times3^{29}-5\times14^5\times2^{12}}{54\times6^{14}\times9^7-12\times8^5\times7^5}\)
tìm x
a,\(\dfrac{6}{7}-\dfrac{3}{4}x=-1\dfrac{1}{2}x-3\)
b\(\left(4x-1\right)^2=\left(4x-1\right)^4\)
c\(\left(\dfrac{4}{5}-\dfrac{3}{4}:x\right)^3=\dfrac{-1}{27}\)
d\(\left|\dfrac{4}{3}-\dfrac{1}{4}x\right|:2\dfrac{1}{3}=0,5\)
giúp mình nhé